Ethical and moral reconstruction in contemporary education: A case study of research in the integrated Islamic junior high school Permata Probolinggo - Prasetiya, Benny; Indiarti, Kinanti (Universitas Ahmad Dahlan, 2024)
This research examines the importance of integrating ethics and morals in education at junior high school level, with a focus on implementation at Permata Integrated Islamic Middle School. This study highlights the implementation of a curriculum that is integrated with Islamic principles and character education, as well as various school programs designed to instill moral values in students. Using qualitative methods, this research found that a curriculum that includes ethical and moral values is successful in shaping student behavior in everyday life. The implementation of programs such as tahfidz, tahsin, and other religious activities, supported by an interactive approach and parental involvement, has proven effective in instilling strong Islamic values. However, this research also notes the challenges faced in the learning process, especially those related to the influence of the home environment and relationships outside of school. Overall, this research concludes that a holistic approach that includes educational interventions, community involvement, and close relationships between schools and parents, is able to create an environment that supports students' ethical and moral development, as well as preparing them to face ethical dilemmas with integrity.